Evolution of Scientific Methods of Content of Preschool Education: from the Times of the Soviet Union to the Independent Ukraine - Frolenkova, Nadiya (Pedagogical Discourse, 2013)
The article deals with the development and establishment of scientific methods of content preschool education from the Soviet Union to an independent Ukraine. The emphasis is on the results of historical and pedagogical analysis of the theory and practice of preschool education. Initial attempts to grasp the origins of software maintenance preschool education since the first decades of the twentieth century are analyzed. They presented in the first theoretical works of the organizers of preschool education in Ukraine. Characteristic to progressive ideas of known domestic educators and social leaders as for development of methodological support of the content of preschool education is given.